Environmental crime and problem-solving courts - White, R. D. (Crime, law and social change, 2013)
Environmental harms are by their nature complex and as such give rise to formal legal responses that range from simple regulatory intervention to multi-faceted court order. The purpose of this paper is to explore the emergence of environmental courts and the development of judicial and tribunal expertise in this specific area. A wide range of sanctions are now available and being actively applied by such bodies. Moreover, in many instances, the philosophical approach adopted by these courts is that of problem-solving. The combination of specialist expertise and innovative methods of intervention are progressively revolutionising judicial practice in regards to contemporary environmental issues.